Effect of functional ankle instability on rebound drop jump - Naruto Yoshida; Shumpei Miyakawa; Toshikazu Miyamoto; Akihiko Masunari; Naoyuki Kobayashi; Eiko Yamada; Hitoshi Shiraki; Tomoo Ishii (Japanese Society of Physical Fitness and Sports Medicine, 2012)
The ankle has an important role in stretch shortening cycle (SSC) movement. Thus, it is likely that ankle instability negatively affects the SSC. To investigate the relation between SSC movement and ankle instability. This could contribute to developing a progressive phase of rehabilitation for athletes after ankle sprain, and could also be used as criteria for returning to sport participation. The legs of eight university male football players were categorized as either having ankle instability (AI group) or not having ankle instability (NI group). Ankle instability was defined as functional instability based on the Karlsson score. The rebound drop jump, which is the index of SSC movement, was measured, and the subjects' performances for SSC movement were evaluated. In addition, isokinetic ankle strength, based on the Biodex System Dynamometer to assess the peak torque of the plantar/dorsal muscles of the ankle joint, was recorded. The groups did not differ in regard to flight time. The contact time of the AI group was significantly longer than that of NI group. With regard to isokinetic ankle strength, there was no significant difference in plantar or dorsal flexion between the two groups. This study showed that the contact time of the AI group was longer than that of NI group. In ankles with instability, the function of the stretch reflex may be suppressed, and the efficiency power for exertion during ballistic SSC movement might thus be decreased. These findings suggest that ankle instability relates to SSC movement by prolonging the contact time in the rebound drop jump.